ERASMUS DEVELOPMENT FROM THE PERSPECTIVE OF STUDENTS: THE CASE OF KLAIPĖDA CITY - Tapınç, Mervan; Öztor, Zeynep; Tüfek, Arif Ertuğrul; Grigaliūnienė, Simona (Lithuania Business University of Applied Sciences, 2023)
In a world that is becoming more globalized, education is one of the top priorities for nations. Countries have started to invest more money into global education. Numerous short and long-term education and exchange arrangements are created with this aim. One of the most popular of these exchange agreements is the Erasmus+ Exchange Program. Based on this, the study sought to examine the causes, incentives, expectations, and experiences that led students participating in the Erasmus+ Exchange Program in Klaipėda, Lithuania, to participate in Erasmus as well as the benefits of Erasmus to students. The study used a qualitative research methodology, and the semi-structured interviewing approach was utilized to gather data. Comparative analysis and content analysis were used for the gathered data. The analyses conducted revealed that most of the expectations of the Erasmusparticipating students were similar. For example, traveling in Europe, socializing, experiencing a different educational system, and language development. Additionally, it has been observed that Erasmus affects students in both positive and negative ways. It has been observed that these effects are within the framework of personal development, education, socialization, language development, and cultural experience. Students who enrol in Erasmus with similar goals and expectations may experience the program in quite diverse ways from one another. It has been noted that most students choose the country for Erasmus, particularly considering economic considerations, and it has been emphasized that in some cases their economic predictions may not come true.
Keywords: Lietuva (Lithuania); Aukštasis mokslas. Studijos / Higher education. Study; Klaipėda. Klaipėdos kraštas (Klaipeda region); Studentai / Students; 4. Education; 16. Peace & justice